2022
DOI: 10.48550/arxiv.2206.06173
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

LiVeR: Lightweight Vehicle Detection and Classification in Real-Time

Abstract: Detection and classification of vehicles are very significant components in an Intelligent-Transportation System. Existing solutions not only use heavy-weight and costly equipment, but also largely depend on constant cloud (Internet) connectivity, as well as adequate uninterrupted power-supply. Such dependencies make these solutions fundamentally impractical considering the possible adversities of outdoor environment as well as requirement of correlated wide-area operation. For practical use, apart from being … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…It was shown that raising the convolution network's depth can be advantageous for computation and classification [22], [23] and [24]. For time-correlated real-time vehicle detection and classification over a large area, an ST-based framework has been presented [25].…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that raising the convolution network's depth can be advantageous for computation and classification [22], [23] and [24]. For time-correlated real-time vehicle detection and classification over a large area, an ST-based framework has been presented [25].…”
Section: Introductionmentioning
confidence: 99%